Oral idarubicin, dexamethasone and vincristine in the treatment of multiple myeloma: final analysis of a phase II trial - Glasmacher, Axel; Goldschmidt, Hartmut; Mezger, Jörg; Haferlach, Torsten; Schmidt-Wolf, Ingo G. H.; Gieseler, Frank (Haematologica, 2004)
This prospective phase II study evaluated a regimen with vincristine, oral idarubicin and dexamethasone (VID) in 74 patients with multiple myeloma. A partial response was achieved in 57% (16/28) of patients with previously untreated disease and in 35% (16/46) with refractory diseases. VID chemotherapy is an effective and tolerable oral alternative in an outpatient setting for these patients.